Kelsea’s Objections against Men’s Stigma in Leading a Kingdom in Johansen’s The Queen of the Tearling - Nissa, Ikka Malia Chairun (Universitas Negeri Semarang, 2019)
Kelsea is a female character in a novel written by Erika Johansen entitled The Queen of The Tearling. When she is nineteen years old, she becomes a queen. Although she has the highest status in her kingdom, sometimes underestimated by men because she is a girl. The purpose of this research is to reveal Kelsea’s objections against men’s stigma in leading a kingdom. This is a qualitative research. The result of this research shows that Kelsea breaks the men’s stigma saying women are weak. Kelsea argues with the general of her army because he thinks women are bad in military strategy. Moreover, Kelsea proves that she has power to dismiss her uncle from her castle because he corrupts and takes the freedom of the women who satisfy him. In addition, Kelsea sets herself equal with her Queen Guards to learn how to fight with sword and wear armor because she will do something while those men die for her. As a conclusion, Kelsea acts as a strong woman with dignity.